Smart Microparticles with a pH-responsive Macropore for Targeted Oral Drug Delivery - Ankit Kumar (Nature Portfolio, 2017)
Abstract The development of a smart microencapsulation system programmed to actively respond to environmental pH change has long been recognized a key technology in pharmaceutical and food sciences. To this end, we developed hollow microparticles (MPs) with self-controlled macropores that respond to environmental pH change, using an Oil-in-Water emulsion technique, for oral drug delivery. We observed that freeze-drying of MPs induced closure of macropores. The closing/opening behavior of macropores was confirmed by exposing MPs encapsulating different ingredients (sulforhodamine b, fluorescent nanoparticles, and lactase) to simulated gastrointestinal (GI) fluids. MPs maintained their intact, closed pore structure in gastric pH, and subsequent exposure to intestinal pH resulted in pore opening and ingredients release. Further, MPs displayed higher protection (>15 times) than commercial lactase formulation, indicating the protective ability of the system against harsh GI conditions. This study showed development of a hybrid MP system combining the advantages of solid particles and hollow capsules, exhibiting easy solvent-free loading mechanism and smart protection/release of encapsulates through controllable macropores. Ultimately, our MPs system strives to usher a new research area in smart drug delivery systems and advance the current oral drug delivery technology by solving major challenges in targeted delivery of pH-sensitive therapeutics.